Government accounting and accounting for non-profit organizations - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2018)
This book has 2 parts, the first part is Government accounting and second part is accounting for non-profit organizations.
1. Overview of government accounting -- 2. The budget process -- 3. The government accounting process -- 4. Revenues and other receipts -- 5. Disbursement -- 6. Financial assets -- 7. Inventories -- 8. Agriculture -- 9. Investment property -- 10. Property, plant and equipment -- 11. Intangible assets -- 12. Liabilities -- 13. Leases -- 14. Financial statements -- 15. Miscellaneous topics -- 16. Non-profit organizations -- 17. Illustrative financial statements of NPOS.
Keywords: ACCOUNTING; ACCOUNTING -- PUBLIC